Extensive changes in the transcriptional profile of human adipose tissue including genes involved in oxidative phosphorylation after a 6‐month exercise intervention. (10th March 2014) - Rönn, T.; Volkov, P.; Tornberg, Å.; Elgzyri, T.; Hansson, O.; Eriksson, K.‐F.; Groop, L.; Ling, C.
Abstract Aim Adipose tissue has an important function in total energy homeostasis, and its dysregulation may contribute to lifestyle‐related diseases such as type 2 diabetes, cancer and cardiovascular diseases. The aim of this study was to investigate genome‐wide mRNA expression in adipose tissue in healthy men before and after an exercise intervention to identify genes or pathways that mediate the beneficial effect of regular exercise. We also investigated the difference in adipose tissue mRNA expression between individuals with or without a family history of type 2 diabetes. Methods The 6‐month supervised exercise intervention was conducted in 47 healthy men (age 37.8 ± 4.3 years, BMI 28.5 ± 3.6 kg m−2) with a previous low level of physical activity. RNA was analysed using GeneChip Human Gene 1.0 ST arrays (Affymetrix) before and after the exercise. Results We identified 2, 560 significant transcripts differentially expressed before vs. after exercise with a false discovery rate (FDR) < 0.1%, including genes encoding the respiratory chain, histone subunits, small nucleolar RNAs and ribosomal proteins. Additionally, pathways enriched in response to exercise include the ribosome, oxidative phosphorylation, proteasome and many metabolic pathways, whereas the WNT and MAPK signalling pathways were down‐regulated (FDR < 5%) after exercise. There were no significant differences in mRNA expression between individuals with or without a family history of type 2 diabetes. Conclusion Exercise increased the expression of genes involved in oxidative phosphorylation, which is the opposite of what has been seen in adipose tissue from elderly or obese individuals with low physical fitness, and our study thereby demonstrates a mechanism for the beneficial effect of exercise.